Threats hidden in stories. Urban legends and security issues: analysis, challenges and perspectives. - Biernat, Marcin (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
This paper presents an introduction to the issue of urban legends in the context of security. For a long time, urban legends have been an integral part of urban culture, playing a role not only in terms of entertainment, but also in shaping perceptions of the world around us. In recent years, there has been a growing interest in the potential impact of urban legends on community security. The submitted article proposes an analysis of this phenomenon, focusing on the complex links between urban legends and aspects of security. By focusing on selected examples, it will be possible to demonstrate the mechanisms by which urban legends emerge and function, as well as the consequences they can cause, including panic and disinformation in the community. The issue also poses challenges in terms of the threats posed by the proliferation of urban legends, and the need to develop strategies to deal with them.